Economic-Environmental Law Guarantee of the Green and Sustainable Development: Role of Health Expenditure and Innovation - Lin Yang (Frontiers Media S.A., 2022)
Environmental regulation is a tool for teaching social and fiscal development that is carbon neutral. The highly polluting food industry in China is a threat to the country's long-term environmental stability and affects public health in a significant way. Therefore, this study investigates the effect of environmental parameters on environmental quality in China's food industry using the cross-sectionally augmented ARDL (CS-ARDL) model over the period of 2010 to 2019. We find that environmental regulations negatively and significantly impact environmental quality. The U-shape relationship exists between environmental regulation and environmental quality. Moreover, government expenditure on health and technological innovation reduces carbon emissions. The study's findings suggest new policy implications supporting the Porter Hypothesis. Finally, this paper offers policy suggestions for China's food industry to enhance its environmental performance.